A DESCRIPTIVE STUDY OF PROSTATE LESIONS IN LARGEST HOSPITAL IN ONDO STATE OF NIGERIA - Adediran, A. O; Olatunbosun, E. I (Global Journal of Health Sciences, 2020)
Purpose: The study aims to retrospectively examine the association between benign prostatic hyperplasia and cancer of the prostate in the largest hospital in Ondo State of Nigeria. Methodology: A descriptive, cross sectional design was used. A total of 286 prostate biopsies were received, processed and analyzed between 2014 and 2018. Necessary information and data generated were retrieved from histopathology request forms, patients' registers and result cards. The concerned section slides were retrieved and reviewed. The research instrument used was the Hematoxylin and Eosin [H&E] staining technique. The photomicrograph of the slides was done in the histopathology laboratory, federal medical centre, Owo using a digital microscope camera attached to an Olympus binocular microscope by placing each slide on the microscope stage well focused for a good capturing and better contrast. Findings: All cases of benign prostatic hyperplasia accounted for 32.2%, nodular hyperplasia was 29.7%, prostate cancers encountered was 30.7% while other lesions accounted for 7.4%. It was found out that prostate cancer affects most men as they get older which leads to urinary problems like those with BPH and prostatitis. They explained that prostate cancer rarely causes symptoms before age 40, but more than half of men in their 60s and most men in their 70s and 80s will have signs of prostate cancer. It was also found out that the occurrence of prostate cancer tended to elevate with increasing age and there was a tendency for the proportion of moderate or severe cases to increase with aging in men. Unique contribution to theory, practice and policy: The study has contributed to knowledge on the high incidence of prostate lesions in Owo, Ondo State. The awareness created by the study should be used to form policy on yearly prostate screening and annual rectal examination of males between 35 to 65 years of age should be carried out since surgical cure could be done before the cells growth leads to a chronic stage.